Bone alkaline phosphatase as a surrogate marker of bone metastasis in gastric cancer patients. Issue 1 (December 2016) - Lim, Sun; Kim, Youn; Park, Ki; Kang, Beodeul; Chon, Hong; Kim, Chan; Kim, Joo; Rha, Sun
Abstract Background Bone metastasis is relatively uncommon in gastric cancer patients, but its incidence has been rising. Early detection of bone metastasis is important in preventing complications related to bone metastasis such as pain, fracture and the compromise of chemotherapy. In this pilot study, we investigated the feasibility of bone turnover markers as surrogate markers of bone metastasis in gastric cancer patients. Methods Fifty-eight patients with gastric cancer were included in this study. Serum levels of bone alkaline phosphatase (ALP), parathyroid hormone (PTH), 25(OH) D, osteocalcin (OC) and C terminal telopeptide were measured and compared between patients with bone metastasis and those without. Student'st -test and Mann-WhitneyU test were used in comparing two groups, and Spearman's rank order correlation coefficient was calculated to quantify the strength of the associations. Results Fifty eight age- and sex-matched patients were evaluated for bone turnover markers, among whom 29 patients had bone metastasis and 29 patients with no bone metastasis. The median age was 62 and there were 20 (68.9 %) males and 9 (31.1 %) females in each group. Bone ALP was significantly higher in the patient group (57.32 ± 46.83 vs. 34.57 ± 21.57, P  = 0.037) than control group. Bone ALP was positively associated with ALP, osteocalcin, CA19-9, CA 72–4 and negatively associated with 25(OH) D. According to ROC-curve analysis, at the threshold value of 29.60 μg/L, the sensitivity of bone ALP was 76.7 % and the specificity was 59.4 %. Conclusion Bone ALP may be a surrogate marker of bone metastasis in gastric cancer patients. More prospective studies are warranted to determine the optimal bone turnover markers in the evaluation of bone metastasis.